STUDENTS’ PERCEPTIONS OF THE USE OF GOOGLE DOCS FOR ONLINE COLLABORATIVE WRITING - Wahyuningsih, Imelda; Herawati, Henny; Prabandari, Carla Sih (LLT Journal: A Journal on Language and Language Teaching, 2023)
The existence of technology, particularly Google Docs, is vital to supporting students in surviving the online learning environment. This research, therefore, aims to investigate students’ perceptions of using Google Docs for online collaborative writing, as well as its benefits and limitations. There are two research questions addressed: (1) What are the students’ perceptions of the use of Google Docs for the ELESP students’ online collaborative? (2) What are the possible benefits and challenges of using Google Docs for the ELESP students’ online collaborative writing? This qualitative case study was conducted at the English Language Education Study Program of Sanata Dharma University. A close-ended questionnaire and semi-structured interview were utilized to collect data. The researchers discovered that most students had positive perceptions of using Google Docs for online collaborative writing. With the aid of its capabilities, Google Docs made online collaborative writing easier and more successful, particularly in students’ performance during group work, communication, and accessibility. Aside from the functionality of Google Docs, students’ active participation was also an important factor for successful online collaborative writing.